2023
DOI: 10.1039/d2na00742h
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-induced formation of Pd nanoparticles in heterogeneous nanobiohybrids: application in C–H activation catalysis

Abstract: The effect of the temperature in the synthesis of Pd nanoparticles in the metal-enzyme biohybrids was evaluated. The effect on the formation, size and morphology of the nanoparticles was evaluated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Recently, although the synthetic approach is well described at room temperature, the temperature phenomenon was evaluated in the case of Pd nanobiohybrids. [39] Synthesis at lower T (4 °C) demonstrated that protein structure modification has a major effect on the final PdNPs formation, where lower but smaller nanoparticles were found using C. antarctica B lipase as protein scaffold. The link between protein structure and temperature, as well as the influence of the latter, has been demonstrated to be critical in the reducing capacity of the enzyme in the final Pd nanoparticle production, metal species, and even nanoparticle size.…”
Section: Synthetic Considerations In the Preparation Of Dual Enzyme-m...mentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, although the synthetic approach is well described at room temperature, the temperature phenomenon was evaluated in the case of Pd nanobiohybrids. [39] Synthesis at lower T (4 °C) demonstrated that protein structure modification has a major effect on the final PdNPs formation, where lower but smaller nanoparticles were found using C. antarctica B lipase as protein scaffold. The link between protein structure and temperature, as well as the influence of the latter, has been demonstrated to be critical in the reducing capacity of the enzyme in the final Pd nanoparticle production, metal species, and even nanoparticle size.…”
Section: Synthetic Considerations In the Preparation Of Dual Enzyme-m...mentioning
confidence: 98%
“…Recently, although the synthetic approach is well described at room temperature, the temperature phenomenon was evaluated in the case of Pd nanobiohybrids [39] . Synthesis at lower T (4 °C) demonstrated that protein structure modification has a major effect on the final PdNPs formation, where lower but smaller nanoparticles were found using C. antarctica B lipase as protein scaffold.…”
Section: Synthetic Considerations In the Preparation Of Dual Enzyme‐m...mentioning
confidence: 99%
“…Due to unique properties of Pd NPs such as high reactivity, selectivity, stability and recyclability, the use of Pd nanocatalyst has been extensively investigated in organic synthesis. 50 For instance, Pd NPs were recently explored in C-H bond activation reactions for heterocyclic compounds functionalization, [51][52][53][54][55][56][57][58][59][60][61] or heterocycles synthesis via cyclization reactions. [62][63][64][65] The synthesis of phenanthridine-6(5H)-ones and benzo[c] chromenes by direct arylation reaction catalyzed by Pd NPs was recently reported.…”
Section: Introductionmentioning
confidence: 99%
“…[4,[15][16][17][18][19][20] Recently, the development of a new sustainable synthetic strategy of metal nanoparticles embedded on enzymes as network scaffold has been described and successfully applied in different CÀ C or CÀ H reactions. [21][22][23][24] The advantages of these methods compared to others are the direct use of a heterogeneous catalyst; the control of the nanoparticle size, where the formation is directly induced by the enzyme; the nanoparticles are homogeneously dispersed on the protein network, avoiding aggregation. Thus, the synthetic process of the formation occurs by an initial coordination of the metal ions in solution with specific amino acid residues on the protein structure (i. e., hydrophobic or negatively charged side chains).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the development of a new sustainable synthetic strategy of metal nanoparticles embedded on enzymes as network scaffold has been described and successfully applied in different C−C or C−H reactions [21–24] . The advantages of these methods compared to others are the direct use of a heterogeneous catalyst; the control of the nanoparticle size, where the formation is directly induced by the enzyme; the nanoparticles are homogeneously dispersed on the protein network, avoiding aggregation.…”
Section: Introductionmentioning
confidence: 99%